Elastic-wave velocity characterization of gas hydrate-bearing fractured reservoirs in a permafrost area of the Qilian Mountain, Northwest China. (December 2017) - Qu, Lu; Zou, Changchun; Lu, Zhenquan; Yu, Changqing; Li, Ning; Zhu, Jichang; Zhang, Xiaohuan; Yue, Xuyuan; Gao, Mingzhe
Abstract: There are two types of gas hydrate-bearing reservoirs in the permafrost area of Qilian Mountain. Most of the gas hydrates occur mainly in the fractured mudstone reservoirs and rarely in the pores of the sandstone reservoirs. In this study, for the acoustic velocity characterization of the fractured gas hydrate reservoirs of the Qilian Mountain permafrost area, some mudstone core samples were collected for physical rock experiments, such as the acoustic experiment and the porosity and permeability experiment. An acoustic velocity numerical simulation of gas hydrate reservoirs was performed according to the Biot theory and the differential effective medium theory, with the conditions of multiple gas hydrate occurrence models, including the suspension model, the semi-cementation model and the cementation model, and considering both infinite and penny-shaped cracks. Fracture porosity was added to the core samples that only contain matrix porosity. With fracture porosity ranging from 0.01% to 5%, the variation laws between acoustic velocity with fractured porosity and hydrate saturation are obtained: (1) In the case of an infinite crack, if the fractured porosity is 0.01%–1%, the P-wave velocity decreases rapidly in the case of the three occurrence models. If the fractured porosity is higher than 1%, the acoustic velocity decreases gradually. If the crack shape is a penny-shaped crack, the P-wave velocity decreases almost linearly with increasing fracture porosity. (2) If the hydrate occurrence model is the suspension model, the P-wave velocity increases slightly with increasing hydrate saturation. If the occurrence model is the semi-cementation model or the cementation model, when the gas hydrate saturation of the infinite crack ranges from 0 to 80%, the acoustic velocity increases approximately linearly, whereas when the gas hydrate saturation ranges from 80% to 100%, the velocity increases rapidly. If the crack is a penny-shaped crack, the velocity increases almost linearly with increasing gas hydrate saturation from 0 to 100%. (3) It is found that the fractured gas hydrate reservoirs of the Qilian Mountain permafrost area contain both penny-shaped and infinite cracks, of which the infinite crack is the main crack shape. The gas hydrate occurrence in the Qilian Mountain permafrost area mainly follows the suspension model. This has significance for the seismic exploration and log evaluation of gas hydrate-bearing fractured reservoirs in the permafrost area of the Qilian Mountain in studying the acoustic velocity characterization, the crack shapes and occurrence models of gas hydrate reservoirs in the study area. Highlights: Biot theory and differential effective medium theory. Variation law between acoustic velocity with fractured porosity. Variation law between acoustic velocity with gas hydrate saturation. The crack shape and occurrence model of gas hydrate reservoir in the Qilian Mountain permafrost area.